Evaluation of Acrylonitrile/Butyl Methacrylate/Halloysite Nanoclay Impregnated Wood Polymer Nanocomposites - Md. Rezaur, Rahman; Chang, Josephine Hui Lai; Sinin, Hamdan (BioResources, 2017)
Acrylonitrile/butyl methacrylate/halloysite nanoclay wood polymer nanocomposites (AN-co-BMA-HNC WPNCs) were prepared via the impregnation method, and the effect of different ratios of polymers was investigated. The WPNCs were characterized through weight percent gain, Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), the three-point flexural test, dynamic mechanical thermal analysis (DMTA), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) analysis, and the moisture absorption test. The weight percent gain in the 50:50 AN-co-BMA-HNC WPNCs was the highest compared with the raw wood (RW) and other WPNCs. The FT-IR results confirmed that polymerization took place in the nanocomposites, especially in the 50:50 AN-co-BMA-HNC WPNCs, with a reduction of hydroxyl groups. The SEM results revealed that the 50:50 AN-co-BMA-HNC WPNCs showed the best surface morphology. The 50:50 AN-co-BMA-HNC WPNCs showed the highest flexural strength and modulus of elasticity. The results revealed that the storage modulus and loss modulus of the AN-co-BMA-HNC WPNCs were higher, while the tan δ of the AN-co-BMA-HNC WPNCs was lower, compared with the RW. The AN-co-BMA-HNC WPNCs also exhibited higher thermal stability and exhibited remarkably lower moisture absorption compared with the RW. Overall, this study demonstrated that the 50:50 AN-co-BMA ratio was the most suitable to be introduced into RW.